Revisiting the issue of legal personality of transnational corporations in private law - Guzel A. Valeeva, Marat R. Suleymanov, (Opción, 2019)
In the modern world, the number of subjects of international law continues to increase. This is due to the increase in commodity circulation and investment activity of business structures. This paper addresses the issue of the essence of the legal personality of transnational corporations as legal entities via analysis, synthesis, comparative method, comparative legal method, methods of dialectics. As a result, The combination of nationality and personal statute creates an enormous difficulty in determining the nationality of legal entities. we can conclude that the basis for the international legal personality of the legal entity is its domestic legal personality